Investigating spatio-temporal distribution and diffusion patterns of the dengue outbreak in Swat, Pakistan - Suleman Atique; Ta-Chien Chan; Chien-Chou Chen; Chien-Yeh Hsu; Somia Iqtidar; Valérie R. Louis; Syed A. Shabbir; Ting-Wu Chuang (Elsevier, 2018)
Introduction: Dengue has been endemic to Pakistan in the last two decades. There was a massive outbreak in the Swat valley in 2013. Here we demonstrate the spatio-temporal clustering and diffusion patterns of the dengue outbreak. Methods: Dengue case data were acquired from the hospital records in the Swat district of Pakistan. Ring maps visualize the distribution and diffusion of the number of cases and incidence of dengue at the level of the union council. We applied space-time scan statistics to identify spatio-temporal clusters. Ordinary least squares and geographically weighted regression models were used to evaluate the impact of elevation, population density, and distance to the river. Results: The results show that dengue distribution is not random, but clustered in space and time in the Swat district. Males constituted 68% of the cases while females accounted for about 32%. A majority of the cases (>55%) were younger than 40 years of age. The southern part was a major hotspot affected by the dengue outbreak in 2013. There are two space-time clusters in the spatio-temporal analysis. GWR and OLS show that population density is a significant explanatory variable for the dengue outbreak, while GWR exhibits better performance in terms of 'R2 = 0.49 and AICc = 700'. Conclusion: Dengue fever is clustered in the southern part of the Swat district. This region is relatively urban in character, with most of the population of the district residing here. There is a need to strengthen the surveillance system for reporting dengue cases in order to respond to future outbreaks in a robust way. Keywords: Dengue, Swat, Pakistan, Spatio-temporal, Clusters, Diffusion